2003
DOI: 10.1063/1.1590409
|View full text |Cite
|
Sign up to set email alerts
|

Below bulk-band-gap photoluminescence at room temperature from heavily P- and B-doped Si nanocrystals

Abstract: Photoluminescence ͑PL͒ properties of heavily P-and B-doped Si nanocrystals ͑nc-Si͒ are studied. By simultaneously doping two types of impurities, nc-Si exhibit strong PL at around 0.9 eV at room temperature. The temperature quenching of the PL is very small. Although the PL peak energy is very close to that of dangling-bond related PL previously observed, all of the observed properties, i.e., decay dynamics, degree of temperature quenching, etc., are apparently different. The transition between donor and accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 26 publications
5
140
1
1
Order By: Relevance
“…This might not prove to be too difficult, once it is recognized as an issue: Recent work on shifting the luminescence spectra of Si nanocrystals indicates that doping with phosphorus or boron may be a simple but effective means of bandgap engineering the peak wavelength of the Si nc PL spectrum [16]. If the Si nc PL can be shifted to the 980-nm (1.2 eV) region, the prospects for efficient optical amplifier and laser operation based on the Er-Si nc material system could be boosted considerably.…”
Section: Discussionmentioning
confidence: 99%
“…This might not prove to be too difficult, once it is recognized as an issue: Recent work on shifting the luminescence spectra of Si nanocrystals indicates that doping with phosphorus or boron may be a simple but effective means of bandgap engineering the peak wavelength of the Si nc PL spectrum [16]. If the Si nc PL can be shifted to the 980-nm (1.2 eV) region, the prospects for efficient optical amplifier and laser operation based on the Er-Si nc material system could be boosted considerably.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Doping of Si NCs in a SiO 2 matrix was performed by introducing the dopant in the matrix before NC formation and subsequently inducing dopant incorporation and Si NC formation simultaneously. 14,[25][26][27][28][29][30] This approach indicated that inclusion of electrically active impurities in Si NCs is kinetically possible (e.g. due to the lack of diffusion), and highlighted the corresponding modification of the NC band structure.…”
Section: Introductionmentioning
confidence: 99%
“…Si NCs embedded in SiO 2 are widely investigated for their novel size-dependent electronic and optoelectronic properties [6][7][8][9][10][11][12][13]. In particular, the exploitation of the properties of such systems in real devices demands an accurate control of their doping.…”
Section: Resultsmentioning
confidence: 99%
“…Doping of semiconductor nanostructures has proven to be distinct from the corresponding bulk materials [1][2][3][4][5] and recently great attention has been focused on developing practical methodologies to dope and control the doping properties of Si nanostructures such, as nanoclusters (NCs) [6][7][8][9][10][11][12][13] and nanowires [14][15][16][17], and on developing theoretical approaches to understand these properties [18][19][20][21][22][23]. The control of doping properties of Si nanostructures allows the fabrication of complex nanomaterials characterized by unpreceded electrical and optoelectronic functionalities.…”
Section: Introductionmentioning
confidence: 99%